The influence of suit size on performance in ski jumping. Part II: field measurements - Elfmark, O.; Müller, S.; Kürschner, M.; Bessone, V.; Krezalek, V.; Virmavirta, M. (Frontiers in Sports and Active Living, 2026)
In the second part of this study (Part II), the purpose was to investigate the influence of suit size on ski jump performance during field experiments. Eight elite ski jumpers from three different nations participated by jumping in training sessions. Three different suits were made for each athlete: Suit 1 was a reference suit with current regulations, i.e., +4 cm larger than the circumference of the body, and the two other suits were respectively 2 cm larger and 2 cm smaller with respect to Suit 1. A total of 133 ski jumps were collected, with the main analysis consisting of 109 jumps as wind measurements were missing for 24 jumps. Suit size had a large influence on performance, with +11.5 pt per suit size (p<0.001), or 3.2 m per cm increase in the circumference of the suit. Wind conditions did not influence the outcome and the results were in line with Part I. It was indicated that the higher level athlete could benefit more from a larger suit after analyzing video of one of the ski jumpers. Inertial measurement unit measurements showed how similar length and even longer jumps could be achieved with lower speeds during the glide by utilizing a larger suit. This indicates that a larger suit could increase safety in ski jumping. However, this needs to be considered in the light of fairness, as a larger suit is more difficult to control, thus a compromise has to be made.